2011
DOI: 10.1364/oe.19.006599
|View full text |Cite
|
Sign up to set email alerts
|

Influence of electron irradiation on optical properties of Bismuth doped silica fibers

Abstract: We report a study of the attenuation spectra transformations for a series of Bismuth (Bi) doped silica fibers with various contents of emission-active Bi centers, which arise as the result of irradiation by a beam of high-energy electrons. The experimental data reveal a substantial decrease of concentration of the Bi centers, associated with the presence of Germanium in silica glass, at increasing the irradiation dose (the resonant-absorption bleaching effect in germano-silicate fiber). In contrast, the spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…The emission lifetime at room temperature typically ranges from hundreds of microseconds to several milliseconds. An additional absorption band at 1400 nm was observed by Dvoyrin et al and Bufetov et al in bismuth doped silica glass [1,[3][4][5]. In a non-oxide glass, Hughes et al reported absorption at ~1180nm, fluorescence lifetime of 175 µs at room temperature for an emission peak at ~1500nm [6].…”
Section: Consequences For Nir-emitting Bi-doped Glassesmentioning
confidence: 82%
See 4 more Smart Citations
“…The emission lifetime at room temperature typically ranges from hundreds of microseconds to several milliseconds. An additional absorption band at 1400 nm was observed by Dvoyrin et al and Bufetov et al in bismuth doped silica glass [1,[3][4][5]. In a non-oxide glass, Hughes et al reported absorption at ~1180nm, fluorescence lifetime of 175 µs at room temperature for an emission peak at ~1500nm [6].…”
Section: Consequences For Nir-emitting Bi-doped Glassesmentioning
confidence: 82%
“…The eutectic of (mol.%) 63 AlCl 3 -37 NaCl was selected as base composition, and the Al:Na ratio was kept constant throughout the study. Noteworthy, excess AlCl 3 facilitates formation of Lewis acidic tetrachloroaluminate AlCl 4 -units which further may stabilize the polycationic species. As raw materials, AlCl 3 (99.9%), NaCl (99.9%), BiCl 3 (99.9%) and Bi powder (99.99%) were employed.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations